Análise da transferência de conhecimento: um estudo multicaso em redes brasileiras de franquias de alimentação - Arruda, Lucas Vilas Boas (2010)
ranchise networks have an intense knowledge transfer strategy, in special at the opening of a new store, when the franchisor transfers a great amount of knowledge to the franchisee. This kind of strategy (called Replication) entails the creation and operation of a large number of similar outlets that deliver the same product or service, exploring the many alternatives of a business model to then use it in a large-scale replication at the exploitation phase. The subtle part of this model is the identification of the correct capabilities that should be replicated and the organizational capability to codify and transfer it to the new units (WINTER; SZULANSKI, 2000; NONAKA; TAKEUCHI, 1997; KOGUT; ZANDER, 1992; MARCH, 1991). The objective of this study is to analyze the opening process of a new franchise unit and detail the knowledge transfer from the franchisor to the franchisee, according the perspective of the franchisor. The franchise segment was chosen both for the importance of the knowledge transfer process in their activities (especially in the relationship with a new franchisee) as for the relevance of the sector in the Brazilian economy. This study analyzed four cases of Brazilian food franchises networks, trying to answer how the franchisor transfers knowledge to a new franchise unit. Following the process for building a research using case studies proposed in the article Building Theories From Case Study Research (Eisenhardt 1989), semi structured interviews were held with the franchisors (owner, Expansion, Training and Relationship managers). Based on those interviews, a detailed analysis of the Exploration and Exploitation phases of each franchise was made, comparing their similarities and differences and identifying the most relevant issues, in the franchisor perspective. The result was a model of Organizational Learning and Knowledge Transfer that summarizes the process of the analyzed franchise networks. It was also possible to confirm the adherence of the Replication model proposed by Winter and Szulanksi (2000), what have corroborated foreign authors’ theories and national works regarding this subject.